Effect of different filler ( Er5356 and Er4043) toward mechanical and microstructure properties of the joint gas metal arc welding Aa6061-T6 - A.A.A., Aziz; M.F.A, Ibrahim; Azman, Jalar; Syarif Junaidi, S Djalil; N.M., Rashdi (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.